SISTEM INFORMASI PENJUALAN HELMET BERBASIS WEB DI ARYA OTO CENTER (Information Technology and Telematics, 2014)
Abstract : Orphanages in the area of ​​Semarang delivery information is very less. Because of all this in the delivery location Orphanage just only on-signpost signpost on the road alone. Thus donors will be difficult to determine where the orphanage really need at for in discordant. Especially at Orphanage located in Semarang is very far from feasible, starting from the location, shelter, beds, even where they learn very much from the word decent. The purpose of the development of information systems to be achieved in this study is developing a web-based information systems that can facilitate public access to information orphanage located in Semarang. Information systems orphanage in Semarang City can be implemented in the form of a website that can be used as a medium of publication contributor orphanage in Semarang City. Keywords: Information Systems, Orphanage, Semarang City